The National Library Service (SBN) towards digital - Sgambati, Giuliana (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2003)
In the sector of technologies for the Information Society, the General Direction for Library Heritage and Cultural Institutes has promoted two programs: · SBN: The National Library Service (Servizio Bibliotecario Nazionale) · BDI: The Italian Digital Library (Biblioteca Digitale Italiana) and another project, which was approved on March 18, 2003: · BDI&NTC: The Italian Digital Library and Cultural Tourist Network